The contribution of healthy nutrition to developing pupils’ competence during physical education and sport lessons: A field study in secondary schools of the Ouled Derradj District, M’Sila Province - Khaoui, Afaf; Sahnoune, Abdelatif; Belkheir, Abdelkader (The International tax journal, 2026)
This study aimed to examine the role of healthy nutrition in developing pupils' competence during physical education and sport (PES) lessons, with a particular focus on the secondary education stage, from the perspective of PES teachers in secondary schools across the Ouled Derradj District of M’Sila Province. A descriptive research design was adopted because of its suitability for the study's nature. The sample comprised 10 PES teachers selected through random sampling. Data were collected via a purpose-designed questionnaire. The main findings indicated (a) a statistically significant positive association between adherence to healthy nutrition and improved pupils' competence during PES lessons, in terms of physical performance as well as endurance and activity levels; (b) pupils who follow a balanced dietary pattern (before, during, and after the lesson) demonstrate better concentration, faster responsiveness, and reduced fatigue than their peers do; and (c) poor dietary habits (such as excessive consumption of sugars, carbonated beverages, and fast food) negatively affect motor performance and increase manifestations of lethargy and exhaustion during the lesson.